On Paranorm Zweier -Convergent Sequence Spaces - Vakeel A. Khan; Khalid Ebadullah; Ayhan Esi; Nazneen Khan; Mohd Shafiq (Journal of Mathematics)
In this paper, we introduce the paranorm Zweier -convergent sequence spaces , , and , a sequence of positive real numbers. We study some topological properties, prove the decomposition theorem, and study some inclusion relations on these spaces.